Rhynophycomicosis in a mule - Carvalho, Eulógio Carlos Queiroz de; Cruz, João Batista da; Nascimento, Ricardo Luiz do (Pesquisa Agropecuaria Brasileira, 2014)
An ulcerated tumour, surgically removed from the Ieft nostril of a mule native or the Rio de Janeiro State, Brazil, was fixed in formol and stained by the Crocott-Gomori, PAS and H.E. methods. The clinical symptoms presented by the mule and the anatomopathological examination results of the collected material made it possible to diagnose, though the etiological agent was not isolated, that it was a case of rhynophycomycosis. Data about phycomycosis forms (mucormycosis, subcutaneous phycomycosis, rhynophycomycosis and hyphomycosis) are given for differential diagnosis. This seems to be the second case of this disease in a mule found in Brazil.